Enterprise Risk Management Models - David L. Olson (Springer, 2023)
This book offers a comprehensive guide to several aspects of risk, including information systems, disaster management, supply chain and disaster management perspectives. A major portion of the book is devoted to presenting a number of operations research models that have been (or could be) applied to enterprise supply risk management, especially from the supply chain perspective. Each chapter of this book can be used as a stand-alone module on a respective topic, with dedicated examples, definitions and discussion notes.